A guerra das palavras: cultura oral e escrita na Revolução de 1817 - Breno Gontijo Andrade (2012)
The purpose of this thesis is to investigate the oral and written culture from 1795 to 1817 in the North of the Portuguese America. First, it shows the importance that the circulation of news and books had in the North region, addressing also how the book market operated in Pernambuco, as well as smuggling and reading. Secondly, it analyses the beginning of the constitution of a public sphere in which eventually several men merged in a common project: the search for an alternative to Absolutist Monarchy of Braganza. Further, it focus in the Pernambucan Revolution of 1817, its birth and expansion, which utilized the oral and written culture,the church structure, and the spread of emissaries. Similarly, realists sought to fight the revolutionaries in the same field, scattering proclamations, convincing not by the force of arms, but by force of words. Finally, we present possible readings and appropriations made in 1817; first of foreign Constitutions for creation of the Organic Law, sort of a pre-Constitution that regulated revolutionized the region; then of the readings of Father John Ribeiro of the works of the philosopher Condorcet and its possible uses in 1817.